2020
DOI: 10.1101/2020.03.09.978627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reshaping of theArabidopsis thalianaproteome landscape and co-regulation of proteins in development and immunity

Abstract: 24Proteome remodeling is a fundamental adaptive response and proteins in complex and 25 functionally related proteins are often co-expressed. Using a deep sampling strategy we 26 define Arabidopsis thaliana tissue core proteomes at around 10,000 proteins per tissue 27 and absolutely quantify (copy numbers per cell) nearly 16,000 proteins throughout the 28 plant lifecycle. A proteome wide survey of global post translational modification revealed 29 amino acid exchanges pointing to potential conservation o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 126 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…Our study of proteins associated with DCP1, DCP2 and DNE1 is more in favor of the second hypothesis and suggests the existence in plants, of a protein complex based on DCP1-DNE1 in parallel of the canonical decapping complex based on DCP1-DCP2. Comparing DCP1, DCP2 and DNE1 protein copies per cell (pcc) as found in a recent global proteomic analysis (Bassal et al, 2020) reveal that DCP1 is the more abundant protein (234128 pcc) followed by DCP2 (67345 pcc) and finally DNE1 (791 pcc). This data supports the existence of a main complex containing DCP2 and of an accessory complex containing DNE1.…”
Section: Discussionmentioning
confidence: 78%
“…Our study of proteins associated with DCP1, DCP2 and DNE1 is more in favor of the second hypothesis and suggests the existence in plants, of a protein complex based on DCP1-DNE1 in parallel of the canonical decapping complex based on DCP1-DCP2. Comparing DCP1, DCP2 and DNE1 protein copies per cell (pcc) as found in a recent global proteomic analysis (Bassal et al, 2020) reveal that DCP1 is the more abundant protein (234128 pcc) followed by DCP2 (67345 pcc) and finally DNE1 (791 pcc). This data supports the existence of a main complex containing DCP2 and of an accessory complex containing DNE1.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have applied single or dual omics to uncover the molecular mechanisms involved in plant–pathogen interactions (Bassal et al ., 2020; Bjornson et al ., 2021; Chen et al ., 2018; Jeon et al ., 2020; Lovelace et al ., 2018; Nobori et al ., 2018, 2020; WinkelmĂŒller et al ., 2021). In this study, we performed a multi‐omics analysis consisting of five omics datasets including metabolome, transcriptome, proteome, ubiquitome and acetylome to systematically elucidate PTI triggered by two different PAMPs in rice.…”
Section: Discussionmentioning
confidence: 99%
“…Like in Arabidopsis , similar PTI‐mediated defence occurs in rice against fungal and bacterial infection, such as ROS production, callose deposition, MAPK signalling cascade activation and the hormone signalling pathways activation (Liu et al ., 2013, 2014; Yang et al ., 2013). Up to now, some single or combined omics studies, including transcriptomic, proteomics and metabolomics, have been reported to investigate the effects of plant responses to invading pathogens or challenged by different PAMPs (Bassal et al ., 2020; Bjornson et al ., 2021; Chen et al ., 2018; Jeon et al ., 2020; Lovelace et al ., 2018; Nobori et al ., 2018; WinkelmĂŒller et al ., 2021). However, an integrative study of multi‐omics data is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…CRKs belong to a large gene family of receptors, but several play important roles in plant defence and immunity (Wrzaczek et al ., 2010). Among these, differential regulation in LYK4 mutants was found for CRK8 , which may act as ROS sensors (Bassal et al ., 2020) as well as CRK9 , which plays a redundant function with CRK4 and CRK5 in ABA signalling (Lu et al ., 2016). The differential regulation of several regulators of MAPK signalling, such as PUB23 and PUB24 (Trujillo et al ., 2008), and MAPK targets, such as WRKY48 (Xing et al ., 2008) and WRKY53 (Wan et al ., 2004), substantiate that LYK4 plays an important role in regulating defence reactions during SA187–Arabidopsis interaction.…”
Section: Discussionmentioning
confidence: 99%